The mitochondrial import gene tomm22 is specifically required for hepatocyte survival and provides a liver regeneration model - Curado, Silvia; Ober, Elke A.; Walsh, Susan; Cortes-Hernandez, Paulina; Verkade, Heather; Koehler, Carla M.; Stainier, Didier Y. R. (Disease Models & Mechanisms, 2010)
Understanding liver development should lead to greater insights into liver diseases and improve therapeutic strategies. In a forward genetic screen for genes regulating liver development in zebrafish, we identified a mutant - oliver - that exhibits liver-specific defects. In oliver mutants, the liver is specified, bile ducts form and hepatocytes differentiate. However, the hepatocytes die shortly after their differentiation, and thus the resulting mutant liver consists mainly of biliary tissue. We identified a mutation in the gene encoding translocase of the outer mitochondrial membrane 22 (Tomm22) as responsible for this phenotype. Mutations in tomm genes have been associated with mitochondrial dysfunction, but most studies on the effect of defective mitochondrial protein translocation have been carried out in cultured cells or unicellular organisms. Therefore, the tomm22 mutant represents an important vertebrate genetic model to study mitochondrial biology and hepatic mitochondrial diseases. We further found that the temporary knockdown of Tomm22 levels by morpholino antisense oligonucleotides causes a specific hepatocyte degeneration phenotype that is reversible: new hepatocytes repopulate the liver as Tomm22 recovers to wild-type levels. The specificity and reversibility of hepatocyte ablation after temporary knockdown of Tomm22 provides an additional model to study liver regeneration, under conditions where most hepatocytes have died. We used this regeneration model to analyze the signaling commonalities between hepatocyte development and regeneration.
Created from Fastlane, Scopus look-up